Evaluasi Sinkronisasi Kerja Alat Muat Dan Alat Angkut Pada PT Modern Widyatehnical Kampung Wiraskadistrik Wanggar Kabupaten Nabire-Papua Tengah - Huby, Gidion Salek Wikirue; Doirebo, Hans Yohanes Elrix (PROMINE, 2025)
PT Modern Widya Tehnical is a construction company in the mining sector engaged in material transportation materials from industrial excavation materials. Mechanical tools in the form of digging tools and transport tools on the reservoir. The current problem shows that the CAT 320 D excavator excavator often waits for the Mithsubishi HD125 PS dump truck to be loaded. The research method was carried out by observing the history of excavating equipment and transportation equipment that were operated and adjusted to the production target. The results of the study obtained the need to add 1 unit of Mitsubishi HD 125 PS dump truck transport equipment so that the efficiency of loading equipment increased from 72.86% to 84%, the difference in increasing the efficiency of loading equipment to 11.14%. This also had an impact on increasing the production of loading equipment by 11.63 m3/hour from 69.75 to 81.38 m3/hour.